Microchamber Device for Detection of Transporter Activity of Adherent Cells - Tsugane, Mamiko; Uejima, Etsuko; Suzuki, Hiroaki (Frontiers in Bioengineering and Biotechnology, 2015)
We present a method to detect the transporter activity of intact adherent cells using a microchamber device. When adherent cells are seeded onto the poly-di-methyl siloxane substrate having microchambers with openings smaller than the size of a cell, the cells form a confluent layer that covers the microchambers, creating minute, confined spaces. As substances exported across the cell membrane accumulate, transporter activity can be detected by observing the fluorescence intensity increase in the microchamber. We tested the microchamber device with HeLa cells over-expressing MDR1, an ATP-binding cassette transporter, and succeeded in detecting the transport of fluorescence-conjugated paclitaxel, the anti-cancer drug, at the single-cell level.